Information literacy and capacity building in academic libraries (2011)
This paper is based on the experience gained from working in academic libraries in Nigeria and an examination of the literature on information skills of library users and information service providers. It discusses the concept of capacity building, information literacy and various challenges facing academic libraries. It highlights capacity building for the libraries as service providers and for the users of the libraries. It is posited that users of library facilities seek information in many more ways than the traditional manual search for books and journals. Inability to get or provide needed information is often a cause for anxiety. Library anxiety and library user anxiety is discussed as well as the role of capacity building, through Information Literacy programmes in reducing or eliminating the anxiety. The need for libraries to provide not only access to the materials, but also to equip library users with skills that will propel them to greater excellence in research is discussed. Recommendations on capacity building for library service providers and library users are also proffered.